Concave octopus-like PtCu nanoframe mediated photo-electro Fenton catalysis for fast organic dyestuff elimination. Issue 13 (10th June 2022) - Yan, Yangyang; Cheng, Shaowen; Zhou, Ping; Li, Heying; Liu, Xiaoran; Lin, Manping; Xie, Feihu; Zhang, Keke; Zhang, Yi; Zhang, Chenyang; Zhao, Shuang; Shi, Jiahua; et al.
Abstract : Pt atom mediates electrooxidation to generate H2 O2, causing a series of Fenton reactions triggered by Cu atom, for further elimination of dyestuff pollutions. The electrocatalytic process provides an acidic pH in solution, a suitable pH range for Fenton catalytic reaction. Abstract : In this work, a photo-electro Fenton catalytic nanoplatform based on concave octopus-like PtCu nanoframes was fabricated for organic dyestuff degradation. The electrochemical oxidation reaction was performed to generate hydrogen peroxide (H2 O2 ) on the interface of PtCu nanoframes via a promising electro-Fenton process for on-demand aqueous remediation.